Return-to-Work Program for Injured Workers: Factors of Successful Return to Employment - Awang, H.; Shahabudin, S.M.; Mansor, Norma (SAGE Publications, 2016)
This study examined the factors of successful return to employment among participants in the return to work program (RTW) following work-related injury. Data were obtained from the Social Security Organization database containing 9850 injured workers who underwent RTW in 2010 to 2013. About 65% had successfully returned to employment. Significant factors of successful return include gender, employer interest, motivation, age, intervention duration, and type of injury. Male and motivated employees were more likely to return to employment compared with female and unmotivated employees, respectively. Participants from interested employers were 23.22 times more likely to return to work than those from uninterested employers, whereas participants whose intervention period exceeded 5 months were 41% less likely to return to work compared with those whose intervention period was within 3 months. Appropriate strategy and enhanced collaboration between the stakeholders would improve the proportion of successful return to employment.